L’écosystème des médias - Nathalie Sonnac (Communication)
Through a literature review, the author analyzes the evolution of the media ecosystem, its main transformations and their socio-economic implications. Her starting point is twofold : information as a common good and the business model of the media conceived as a multi-platform of exchange. Through a series of socio-political questioning, she studies the impact on media content of dual financing, in terms of pluralism, diversity, quality and the role of the State within media industries.